Evaluasi teknologi pencahayaan untuk ruangan kelas pada Pondok Pesantren Khairul Ummah - Azriyenni Azriyenni; Amir Hamzah; Riski Febriyursandi; Fri Murdiya; Nurhalim Nurhalim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Lighting on an excellent classroom will create comfort in every activity is very important. The installation and availability of light points and types of views that are good and right can affect the lighting conditions in a classroom. The problem is the installation of lights and types of lights that are not following the standards used in Indonesia, and it will cause harm to humans in the form of disturbances in eye function. The purpose of this community service is to improve proper lighting technology in several classes in MA and MTs of the Islamic Boarding School at Khairul Ummah. Then, improve the quality of light and lighting in a few the classroom based on software. The method that will be implemented in this community service is designing and techniques of lighting that are good using the software, namely DIALux Evo 8.1.